Armenia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper describes economic developments in the Republic of Armenia during 1990s. The lagged effects of the more expansionary stance of late 1996, combined with real shocks in early 1997, especially poor weather, and a loss in the momentum in structural reform, particularly privatization, led to a slowdown in growth to about 3 percent during the first nine months of 1997 compared with the same period in 1996. Inflation, measured by the 12-month increase in consumer prices, rose to 23 percent by end-September 1997 from 16 1\2 percent a year earlier.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet